Comparative assessment level of compliance and dental status of mentally retarded children - O. V. Gulenko; V. V. Volobuev; N. I. Bykova; E. A. Faraponova; S. B. Hagurova (Кубанский научный медицинский вестник, 2015)
The absence of mentally retarded children readiness to dental treatment entails significant costs for the individual and for society, exacerbating dental pathology. Therefore, the identification of patients with a low level of compliance in the future will help them to focus on their influence and to focus on the necessary dental procedures, in order to increase the level of motivation for treatment. In a study of dental status of school-age mentally retarded children of varying severity were found higher rates of oral hygiene, caries and periodontal disease compared to healthy. In addition, the results of the survey indicate a lower level of compliance of mentally retarded children and their parents.